Fabrication of nano-crystalline silicon thin film on flexible substrate by cathodic vacuum arc - Lin, T.-Y. (2014)
2009 International Display Manufacturing Conference, 3D Systems and Applications, and Asia Display, IDMC/3DSA/Asia Display 2009